2017
DOI: 10.12659/msm.899855
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dexmedetomidine on Oxidative Stress Response Following Cerebral Ischemia-Reperfusion in Rats and the Expression of Intracellular Adhesion Molecule-1 (ICAM-1) and S100B

Abstract: BackgroundIschemia-reperfusion injury of whole brain involves a complicated pathophysiology mechanism. Dexmedetomidine (Dex) has been shown to have neuro protective functions. This study observed the effect of Dex on serum S100B and cerebral intracellular adhesion molecule-1 (ICAM-1) in a rat model of cerebral ischemia-reperfusion.Material/MethodsHealthy Sprague Dawley (SD) rats (males, 7 weeks old) were randomly divided into sham, model, and Dex groups (n=20 each). A cerebral ischemia-reperfusion model was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Furthermore, we found that APE1 knockdown induced by APE1 shRNA abolished resveratrol-induced the increases in the cell viability and decreases in the LDH release, indicating the contribution of APE1 to the protective effect of resveratrol against OGD/R injury. Increasing evidence confirms that inhibition of oxidative stress of and promotion of antioxidant signaling contributes to neuroprotective agent against ischemia-reperfusion damage to rat brains (35,36). APE1 is a multifunctional protein that plays a vital role in the cellular response to DNA injury and redox regulation against oxidative stress through the inhibition of reactive oxygen species (ROS) production (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that APE1 knockdown induced by APE1 shRNA abolished resveratrol-induced the increases in the cell viability and decreases in the LDH release, indicating the contribution of APE1 to the protective effect of resveratrol against OGD/R injury. Increasing evidence confirms that inhibition of oxidative stress of and promotion of antioxidant signaling contributes to neuroprotective agent against ischemia-reperfusion damage to rat brains (35,36). APE1 is a multifunctional protein that plays a vital role in the cellular response to DNA injury and redox regulation against oxidative stress through the inhibition of reactive oxygen species (ROS) production (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thiopental pretreatment reduced renal IR injury induced by free radicals [46, 47]. Reinforcing this finding, dexmedetomidine has been shown to decrease brain IR injury and inhibit nuclear factor-κB and intercellular adhesion molecule 1 expression through the inhibition of oxidative stress and inflammation, which are pathogenic factors of IR injury [48]…”
Section: General Anesthesiamentioning
confidence: 94%
“…Simultaneously, inflammatory cells that accumulate in the ischemic area release large amounts of toxic oxygen free radicals, proteolytic enzymes, and related molecules, thus increasing vascular permeability, destroying the blood-brain barrier, and causing toxic damage to neurons (Yang et al, 2018). Dexmedetomidine alleviates ischemia-reperfusion damage to rat brains and inhibits NF-κB and ICAM-1 expression in brain tissues (Li and Liu, 2017).…”
Section: Icam-1mentioning
confidence: 99%